2022
DOI: 10.1002/pds.5490
|View full text |Cite
|
Sign up to set email alerts
|

Core concepts in pharmacoepidemiology: Measures of drug utilization based on individual‐level drug dispensing data

Abstract: Background Drug utilization studies are essential to facilitate rational drug use in the society. Aim In this review, we provide an overview of drug utilization measures that can be used with individual‐level drug dispensing data, referencing additional reading on the individual analysis. This is intended to serve as a primer for those new to drug utilization research and a shortlist from which researchers can identify useful analytical approaches when designing their drug utilization study. Results and Discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
31

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 57 publications
0
16
0
31
Order By: Relevance
“…However, at least the duration of exposure to osteoporosis medications was appropriately defined through the implementation of the refill-gap method, which is standard in pharmacoepidemiologic studies, and through the specification of a clinically plausible grace period. 14 To account for imprecisions in the diagnostic terms, the definitions of outcome variables and comorbidity variables in this study were defined based on the findings of previous validation studies. For example, the definition of CVD based on a combination of disease/procedure codes, medications, as well as testing, guarantees a high positive predictive value for true CVD events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at least the duration of exposure to osteoporosis medications was appropriately defined through the implementation of the refill-gap method, which is standard in pharmacoepidemiologic studies, and through the specification of a clinically plausible grace period. 14 To account for imprecisions in the diagnostic terms, the definitions of outcome variables and comorbidity variables in this study were defined based on the findings of previous validation studies. For example, the definition of CVD based on a combination of disease/procedure codes, medications, as well as testing, guarantees a high positive predictive value for true CVD events.…”
Section: Discussionmentioning
confidence: 99%
“…This was a cohort study using a new-user, active comparator approach. 14,15 Patients who met all of the following four criteria were included: (1) age ≥ 40 years; (2) ICD-10 code "osteoporosis with/without pathological fractures" or experiencing fragility fractures 16 ; (3) new prescription of either romosozumab (WHO-ATC code: M05BX06) or bisphosphonate; and (4) prescription date later than March 4, 2019 ( eTable 1) . Patients whose diagnosis code included "suspect" were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discontinuation of anti-coagulation was established according to the refill-gap method; those with a temporal gap between consecutive prescriptions of greater than sixty days, not filled by the penultimate prescription, were defined as having discontinued. (14) Prescriptions of oral anti-coagulants were determined from the PIS; this dataset comprises records for all prescribed drugs dispensed by community pharmacies, in addition to dispending physicians and suppliers of medical devices. (15) To ensure that the indication for the anti-coagulant prescription was exclusively AF, Individuals with valvular heart disease, a mechanical cardiac valve, or venous thromboembolism, were excluded from analyses (Table S3).…”
Section: Methodsmentioning
confidence: 99%
“…Use of psychotropic medications is often considered a proxy for the mental health status of a population or for the prevalence of specific mental disorders . Population-based studies have reported increases in the uptake of antidepressants and hypnotics among youths (<18 or 19 years) in the months following the pandemic onset .…”
Section: Introductionmentioning
confidence: 99%